34.1.3 problem 3

Internal problem ID [6027]
Book : A treatise on ordinary and partial differential equations by William Woolsey Johnson. 1913
Section : Chapter 1, Nature and meaning of a differential equation between two variables. page 12
Problem number : 3
Date solved : Monday, January 27, 2025 at 01:33:37 PM
CAS classification : [[_homogeneous, `class A`], _rational, _dAlembert]

\begin{align*} y {y^{\prime }}^{2}+2 x y^{\prime }-y&=0 \end{align*}

Solution by Maple

Time used: 0.034 (sec). Leaf size: 69

dsolve(y(x)*diff(y(x),x)^2+2*x*diff(y(x),x)-y(x)=0,y(x), singsol=all)
 
\begin{align*} y &= -i x \\ y &= i x \\ y &= 0 \\ y &= \sqrt {c_1 \left (c_1 -2 x \right )} \\ y &= \sqrt {c_1 \left (c_1 +2 x \right )} \\ y &= -\sqrt {c_1 \left (c_1 -2 x \right )} \\ y &= -\sqrt {c_1 \left (c_1 +2 x \right )} \\ \end{align*}

Solution by Mathematica

Time used: 0.465 (sec). Leaf size: 126

DSolve[y[x]*(D[y[x],x])^2+2*x*D[y[x],x]-y[x]==0,y[x],x,IncludeSingularSolutions -> True]
 
\begin{align*} y(x)\to -e^{\frac {c_1}{2}} \sqrt {-2 x+e^{c_1}} \\ y(x)\to e^{\frac {c_1}{2}} \sqrt {-2 x+e^{c_1}} \\ y(x)\to -e^{\frac {c_1}{2}} \sqrt {2 x+e^{c_1}} \\ y(x)\to e^{\frac {c_1}{2}} \sqrt {2 x+e^{c_1}} \\ y(x)\to 0 \\ y(x)\to -i x \\ y(x)\to i x \\ \end{align*}